Analysis of grassroots innovation practice towards sustainable development in Malaysia - Amir Syah, Fandi Ahmad Shah; Abd Rahman, Khairul Aidil Azlin; Ja’afar, Mohamad Fakri Zaky; Mohd Yunos, Mohd Yazid (UNIMAS Publisher, 2021)
Grassroots innovation is an activity that uses multiple resources or indigenous technology to create an innovation more creatively. The innovations are often utilised to improvise the community and environment. The invented product or process is created at the bottom of the pyramid due to necessities, difficulties, and challenges. Malaysia thrives to become a high income developed nation through several initiatives, such as lifelong learning and innovation. Malaysians are encouraged to undertake education programmes to enhance knowledge and skills. These grassroots activities need to be discovered as they affect income and social values. The local grassroots innovators have difficulty commercialising the innovations due to a lack of skills, knowledge, and technology. This study aimed to identify the grassroots innovations, the process in developing innovation, and complement the innovation towards commercialisation. Local innovators adapt to the new product development process as a mutual understanding and for grassroots sustainable development.